Asbestos fibre burden in gallbladder: A case study. (February 2018) - Croce, Alessandro; Capella, Silvana; Belluso, Elena; Grosso, Federica; Mariani, Narciso; Libener, Roberta; Rinaudo, Caterina
Highlights: Characterization of asbestos fibres in histological sections. Quantification of asbestos fibres in gallbladder from mesothelioma patients. Quantification of fibres in limited amount of tissues. Application of two methods for fibre quantification. Abstract: The methods conventionally used to determine the burden of asbestos fibres inhaled/incorporated in lung require chemical digestion of the biological matrix before counting/characterising the inorganic fibrous phases under scanning electron microscopy and energy dispersive spectroscopy (SEM/EDS). Asbestos fibres can also be present in extra-pulmonary organs, and we set out to quantify the fibres in gallbladder. Although the standardised procedure requires approximately 5 × 10 −1 g of wet tissue, this amount of tissue is not always available. We applied the procedure on about 9 × 10 −4 g of gallbladder from a patient with known environmental and workplace exposure to asbestos. The patient died of malignant pleural mesothelioma and was also affected by severe bile-tract problems. The traditional procedure of digesting tissue samples in NaClO and filtering the resulting suspension was carried out. The filter was then examined under SEM/EDS using two methods 1. following the standardised procedure to assess the fibre burden in lung by investigating only 2 mm 2 of the filter (660 microscopic fields), and 2. analysing all the microscopic fields in one-quarter of the filter (about 82 mm 2 ). In parallel, histological sections (prepared in the usual way for medical diagnosis) were analysed without digestion or manipulation of the sample using variable pressure SEM/EDS. The fibre counts obtained using the two methods were of the same order of magnitude, i.e., ∼10 5 fibres/g of wet tissue. We showed that the counting of fibres in human tissue may be successfully carried out even when a limited amount of tissue is available. We also found that, when exposure to asbestos is considerable, the number of asbestos fibres accumulating in the gallbladder may be significant.